John of Tella's Profession of faith: The legacy of a sixth-century Syrian Orthodox bishop - Johannes, Bar Qursos 482-538 (Texts from Christian late antiquity, 2009)
The aftermath of the Council of Chalcedon (451) -- The author : John of Tella -- John's career : from monk to bishop -- John of Tella as an author -- John of Tella's Profession of faith -- The manuscript British Library add. 14549 -- The title Profession of faith -- Structure of the Profession of faith -- John's list of heretics -- John's christology -- Date of John's Profession of faith -- John of Tella, the Apostle Paul, and the foundation of the church -- John of Tella's ecclesiology -- Conclusion: A bishop's spiritual legacy -- Notes on the edition and translation -- Text and translation -- The faith of the venerable and holy Bishop of Tella